Aesthetics of Ecoprint with Quilting Technique Application on Fashion Products - Pingki Aulia Agustin; Esty Nurbaity Arrsyi (Journal of Creative Industries and Vocational Innovation, 2025)
This research aims to obtain ecoprint aesthetic results of the application of quilting techniques on fashion products as assessed by 4 expert panelists based on A.A.M Djelantik's aesthetic theory with indicators of form/appearance, weight/content and appearance/presentation. The research method uses quantitative descriptive with pre-experimental design, one shot case study and data analysis techniques use descriptive statistics. The fashion products made are in the form of 5 vest designs with different design placement. The data collection technique uses mixed lifting. The overall aesthetic results based on aspects of form/appearance, weight/content and appearance/presentation obtained a percentage score of 90% in the very good category. The shape/form indicator consists of design elements and principles, namely shape, color, texture, harmony, rhythm and proportion, which received the highest percentage score of 91%. The weight/content indicator is based on ideas, the source of inspiration used is "Poppy Fields" which received the second highest score of 90% in the very good category. The appearance/presentation indicator based on means/media received the lowest score of 89% in the very good category. The product with the highest rating was design 2, namely 95%, and the lowest score was obtained by designs 3 and 4, namely 88%, with a very good category among the five design products.